Mature-aged students' experiences of learning online in regional and remote Australia: an ecological systems perspective. (1st July 2022) - Crawford, Nicole; Emery, Sherridan; Stone, Cathy
University students who live and work in regional, rural and remote areas face challenges in studying at a distance from their institution's metropolitan or satellite campus. For mature-aged students in particular, relocating to a city campus is unrealistic, due to their family and employment commitments, and travel time and costs. A pragmatic alternative embraced by high proportions of mature-aged students is to study online. However, learning online has welldocumented difficulties. This article explores the online learning experiences of mature-aged university students in regional and remote Australia via students' individual stories in the form of three vignettes . Bronfenbrenner's ecological systems model is employed to analyse the vignettes for systemic and structural factors that condition the students' experiences. This theoretical frame affords new insights into the challenges of learning online. We found that influences beyond the actions of individual students and staff, such as students' internet access and the casualisation of the university workforce, help explain why staff working 'on the ground' may not always be able to provide 'quality' curriculum and support for online students. Placing experiences of individual students within larger contexts uncovers how institutional elements and broader higher education policy can influence the learning for students studying online.